2007
DOI: 10.1179/016164107x166272
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous regional and temporal energetic impairment following controlled cortical impact injury in rats

Abstract: OBJECTIVES: Following traumatic brain injury metabolic stability is impaired. Duration and reversibility of these changes might be important to guide specific interventions. METHODS: To characterize temporal and regional changes in cerebral metabolism, 68 male Sprague-Dawley rats were subjected to a focal cortical contusion. Lesion progression and mitochondrial impairment were determined by magnetic resonance imaging (MRI) and triphenyl tetrazolium chloride (TTC) staining, respectively. Metabolic alterations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Previously, it was found that different cortical contusion zones ranging from the injury center, through its periphery, to the surrounding penumbra, display specific pathological characteristics, e.g., blood flow and oxygenation, in both human and experimental TBI. [43][44][45][46][47] Considering the dependence of mitochondrial structure and energetics on the availability of biofuel and oxygen, the differences in mitochondrial morphology among these zones is consistent with these gradients.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, it was found that different cortical contusion zones ranging from the injury center, through its periphery, to the surrounding penumbra, display specific pathological characteristics, e.g., blood flow and oxygenation, in both human and experimental TBI. [43][44][45][46][47] Considering the dependence of mitochondrial structure and energetics on the availability of biofuel and oxygen, the differences in mitochondrial morphology among these zones is consistent with these gradients.…”
Section: Discussionmentioning
confidence: 97%
“…First, in the Fx/TBI-group TBI was induced using the CCI-method [11,12]. After prone positioning of the mouse and fixation of the skull in a stereotactic device (Stoelting, Wood Dale, IL) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Increased lactate/glucose (L/Glc) ratio reflects sustained lactate production driven by hypoxia-induced and ischemia-induced hyperglycolysis encountered following TBI [24-27] and unmasks functional adaptation processes. Although elevated L/Glc ratio is associated with worse outcome [27], lactate has also been shown to fuel energy-requiring processes.…”
Section: Introductionmentioning
confidence: 99%